2020
DOI: 10.3390/ijerph17103444
|View full text |Cite
|
Sign up to set email alerts
|

A Comparison between Cigarette Topography from a One-Week Natural Environment Study to FTC/ISO, Health Canada, and Massachusetts Department of Public Health Puff Profile Standards

Abstract: Standardized topography protocols for testing cigarette emissions include the Federal Trade Commission/International Standard Organization (FTC/ISO), the Massachusetts Department of Health (MDPH), and Health Canada (HC). Data are lacking for how well these protocols represent actual use behavior. This study aims to compare puff protocol standards to actual use topography measured in natural environments across a range of cigarette brands. Current smokers between 18 and 65 years of age were recruited. Each part… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
25
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
2
1

Relationship

4
5

Authors

Journals

citations
Cited by 16 publications
(25 citation statements)
references
References 10 publications
0
25
0
Order By: Relevance
“…Despite of that, not all correlations between the 3 nicotine biomarkers (Nequ, plasma Cot and saliva Cot) and the daily consumption on Day 3 were found to be statistically significant ( Table 3 ), indicating that other product use factors, in addition to daily consumption, are pivotal for the nicotine uptake. For the inhalation products (CC, EC, HTP), puffing topography as well as extent of inhalation (depth and duration) are assumed to be important determinants for the uptake of smoke/aerosol constituents ( Appleton et al, 2015 , Jones et al, 2020 , Robinson et al, 2020 , Vansickel et al, 2018 ). A striking finding was that no correlation at all was observed between the nicotine biomarkers and number of puffs in vapers ( Table 3 ).…”
Section: Discussionmentioning
confidence: 99%
“…Despite of that, not all correlations between the 3 nicotine biomarkers (Nequ, plasma Cot and saliva Cot) and the daily consumption on Day 3 were found to be statistically significant ( Table 3 ), indicating that other product use factors, in addition to daily consumption, are pivotal for the nicotine uptake. For the inhalation products (CC, EC, HTP), puffing topography as well as extent of inhalation (depth and duration) are assumed to be important determinants for the uptake of smoke/aerosol constituents ( Appleton et al, 2015 , Jones et al, 2020 , Robinson et al, 2020 , Vansickel et al, 2018 ). A striking finding was that no correlation at all was observed between the nicotine biomarkers and number of puffs in vapers ( Table 3 ).…”
Section: Discussionmentioning
confidence: 99%
“…This is currently a focus of our future development. For this, we will leverage our wPUM topography monitors [ 27 ] to identify the start and end of a puff relative to the lung volume waveform measured by the WRM. This will help in discriminating the breaths that are associated with smoking from the natural tidal breaths.…”
Section: Discussionmentioning
confidence: 99%
“…Some studies have reported emissions in terms of the HPHC mass ratio, f HPHC (mg/mg) (i.e., the mass of selected HPHCs per unit mass of TPM) (17,26,30,31,33). Previously proposed smoking machine standards such as (34) provided a basis for product comparisons but did not reflect the range of user behaviors observed (35), thus limiting their utility for public health assessments. Similarly, recent vaping machine standards (36) provide some basis for product comparisons, but also do not reflect the range of use behavior anticipated in the natural environment.…”
Section: Introductionmentioning
confidence: 99%